Ungkapan Sejarah-Simbolik Prabu Airlangga dalam Kakawin Lambang Pralambang - Naufal Anggito Yudhistira; I Made Suparta (Jumantara: Jurnal Manuskrip Nusantara, 2022)
Kakawin Lambaᶇ Pralambaᶇ is an Old Javanese poet in the bhāṣa genre written in Lombok and contained in a manuscript coded CP.25 LT-223, in FSUI collection. This work contains lyrics with erotic-romantic themes, although there is a symbolic story of King Airlangga. The purpose of this study is to reveal the content of the text through philological work and identify the symbolic elements of King Airlangga in it. This research is qualitative research using a philological method based on one manuscript or codex unicus. This study also uses a reception approach. After doing philological work on the text, it can be seen that KLP is framed in the kakawin meter, has 8 chapters, has a romantic-erotic theme, and has a uniqueness in the form of a symbolic story of King Airlangga. The symbolism related to King Airlangga can be seen from the mention of his name, his majesty, to the sraddha ceremony being discussed. The element is seen as a collective memory stored in the text. The conclusion of this research is that the symbolic image of King Airlangga in the Kakawin Lambaᶇ Pralambaᶇ text is a form of collective memory in Old Javanese literature in Lombok.